2018
DOI: 10.1002/ptr.6027
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective effects of dammarane sapogenins against 60Co‐induced myelosuppression in mice

Abstract: Radiotherapy frequently induces failure of hematopoietic system and leads to myelosuppression. The objective of this study was to investigate the protective effect of dammarane sapogenins (DS), the hydrolysed product of the constituent ginsenosides of Panax ginseng, which are produced by gut metabolism, on radiation-induced hematopoietic injury. Mice were exposed to 3.5 Gy Co γ-rays of total body radiation at a dose rate of 1.60 Gy per minute and treated with DS or granulocyte colony-stimulating factor immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Furthermore, the MWM task was carried out to examine long‐term, spatial learning, and memory, which required the animals to remember and locate a submerged escape platform according to the distal cues (Lv, Yang, Li, & Yuan, 2020). Consistent with the published reports (Dong et al, 2018; Lu, Lv, Dong, et al, 2018; Lu, Wang, Lv, et al, 2018; Lu, Wang, Wang, et al, 2018; Lu, Wang, Xu, et al, 2018), CSD model mice showed the prolonged escape latency in the acquisition phase and the decreased crossing numbers in the probe phase. Meanwhile, SI treatment effectively promoted the learning and memory performance of CSD‐treated mice in MWM task, which was in line with the previous finding that SI improved the cognitive function of the ethanol‐induced dementia mice in MWM experiment (Lu et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the MWM task was carried out to examine long‐term, spatial learning, and memory, which required the animals to remember and locate a submerged escape platform according to the distal cues (Lv, Yang, Li, & Yuan, 2020). Consistent with the published reports (Dong et al, 2018; Lu, Lv, Dong, et al, 2018; Lu, Wang, Lv, et al, 2018; Lu, Wang, Wang, et al, 2018; Lu, Wang, Xu, et al, 2018), CSD model mice showed the prolonged escape latency in the acquisition phase and the decreased crossing numbers in the probe phase. Meanwhile, SI treatment effectively promoted the learning and memory performance of CSD‐treated mice in MWM task, which was in line with the previous finding that SI improved the cognitive function of the ethanol‐induced dementia mice in MWM experiment (Lu et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the MWM task was carried out to examine long-term, spatial learning, and memory, which required the animals to remember and locate a submerged escape platform according to the distal cues (Lv, Yang, Li, & Yuan, 2020). Consistent with the published reports (Dong et al, 2018;Lu, Lv, Dong, et al, 2018;Lu, Wang, Xu, et al, 2018), CSD model mice showed the prolonged escape latency in the acquisition phase and the decreased crossing numbers in the probe phase.…”
Section: Discussionmentioning
confidence: 73%
“…Ginsenosides, the major active constituents of ginseng, possess cognitive‐enhancing, antidepressant and anxiolytic effects (Feng et al, 2016; Ru et al, 2015). Dammarane sapogenins (DS) is an extract derived from ginseng by alkaline hydrolysis of total ginsenosides, and contains protopanaxatriol (PPT, 33%) and protopanaxadiol (PPD, 16%) as main ingredients (Figure 1) (Dong et al, 2018; Kong et al, 2013). It has been demonstrated that DS possesses high pharmacological activity and has higher bioavailability than ginsenosides and may therefore have a more potent clinical effect (Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to develop safe and effective radioprotectors to modify the natural response of hematopoietic system to radiation-induced toxicity or fatality. In this regard, histological analysis of bone marrow has demonstrated that pre-treatment with radioprotective agents such as roxadustat, dammarane sapogenins, CpG-oligodeoxy nucleotides (ODN), homogeneous polysaccharides ( APS-1a and APS-3a), chlorobenzylsulfone derivative (ON 01210.Na), 17-dimethylaminoethylamino-17- demethoxygeldanamycin, ascorbic acid, δ-tocotrienol (DT3) and genistein improves the cellularity in bone marrow and ameliorates hematopoietic toxicity in mice [ 18 , 21 - 24 , 27 - 30 ]. Recently, it was reported that telmisartan protected testis and reproduction organs against radiation-induced toxicity in animal models.…”
Section: Discussionmentioning
confidence: 99%